Metabolički parametri u oslabljenoj toleranciji glukoze sa ili bez osnovne ishemijske bolesti srca - Brkić, Milena; Đekić, Danijel; Jovanić, Jelena; Topić, Goran; Grbić, Aleksandra; Šutilović, Tatjana (Scripta Medica, 2022)
Background/Aim: The evidence showed that in the development of diabetes mellitus type 2 (DMT2) and coronary heart disease (CHD) significant role is played by metabolic risk factors: insulin resistance (IR), dyslipidaemia and obesity. Beside metabolic factors, increase in inflammatory markers such as fibrinogen and hs-C reactive protein (hsCRP) plays a role in developing CHD. Metabolic disorders are thought to also be present in patients with impaired glucose tolerance (IGT) and could contribute to development of CHD in these individuals. Aim of this study was to investigate the behaviour of metabolic parameters and chronic inflammation markers in patients with IGT on glucose tolerance test and associated CHD. Methods: The trial included 4 groups of 30 subjects: a) IGT with CHD, b) IGT without CHD, c) CHD without IGT and d) control group without CHD and with normal glucose tolerance (NGT). Within each group glucoregulation parameters were measured (fasting glucose and Hb1Ac). Oral glucose tolerance test (OGTT) with 75 g glucose load was performed and IR parameters calculated (using HOMA-IR, Matsuda index, Quicki index, HOMA1- %B), lipid profile was done, waist/hip ratio was measured, as well as fibrinogen and hsCRP. CHD diagnosis was determined by typical signs of previous myocardial infarction on ECG, echocardiogram and/or ergometry (Bruce protocol). Results: Subjects with IGT, but no CHD and those with both IGT and CHD had statistically significantly higher triglyceride and cholesterol levels and manifest IR with decreased insulin sensitivity compared to subjects with CHD, but no IGT and control group. Group with both IGT and CHD was found to have significantly higher fibrinogen and hsCRP concentrations. Conclusion: IR and hyperlipidaemia, together with chronic inflammation mediators, are potential predictors of the development of glucose tolerance disorders; hence interventional treatment during IGT period or during hyperinsulinaemia could give patients better opportunity to prevent or postpone onset or development of diabetes and its complications.